BASLAWÍSh KLASS OQÍWShÍLARÍNA “ANA TILI HÁM OQÍW SAWATLÍLÍǴÍ” HÁM “SÚWRETLEW ÓNERI” PÁNLERIN INTEGRACIYALAP OQÍTÍWDÍŃ MAZMUNÍ - Muratkamalova, R.J. (SCIENCE and SOCIETY, 2025)
This article discusses the development of visual arts and native language and reading literacy in general education schools based on an integrative approach.